Determinan pendapatan pelaku usaha mikro kuliner di Kota Jambi - Irwanto, Ajis; Zulfanetti, Zulfanetti; Umiyati, Etik (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
Unemployment of educated workers is a problem in the workforce, especially in Jambi City. This study aims to: 1) analyze the characteristics of educated workforce in obtaining a job in Jambi City, 2) analyze the factors that affect the length of time to seek work for educated workers in obtaining a job in Jambi City. This research uses multiple linear regression formulation.The results showed that the characteristics of the educated workforce who became respondents according to the average age of educated workers, namely 28 years, the dominant gender of the respondents was male. According to the latest level of education of educated workers, the average is 15 years, the average work experience of educated workers is never worked, the income of parents of educated workers is Rp. 2,513,043 on average, and the average length of time looking for work for workers is Rp. educated workforce is 1 year. Based on the results of the study, it shows that education, parents' income, and work experience affect the length of time looking for work for educated workers in Jambi City.